2014
DOI: 10.1103/physrevd.90.023012
|View full text |Cite
|
Sign up to set email alerts
|

Curvature versus distances: Testing the FLRW cosmology

Abstract: We test the FLRW cosmology by reconstructing in a model-independent way both the Hubble parameter H(z) and the comoving distance D(z) via the most recent Hubble and Supernovae Ia data. In particular we use: data binning with direct error propagation, the principal component analysis, the genetic algorithms and the Padé approximation. Using our reconstructions we evaluate the Clarkson et al test known as ΩK (z), whose value is constant in redshift for the standard cosmological model, but deviates elsewise. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 90 publications
3
105
0
Order By: Relevance
“…Redundancy -observing the same thing in different ways -is often invoked (and sold to the funding agencies) as a way to control systematics, but can also be used to perform effective null tests of ΛCDM predictions. A number of tests of fundamental assumptions such as the Copernican Principle and statistical homogeneity that use redundant distance and spatial curvature measurements have been proposed, for example [53,54,55,56].…”
Section: Observing Dark Energy In the Era Of Large Surveys Plenary Spmentioning
confidence: 99%
“…Redundancy -observing the same thing in different ways -is often invoked (and sold to the funding agencies) as a way to control systematics, but can also be used to perform effective null tests of ΛCDM predictions. A number of tests of fundamental assumptions such as the Copernican Principle and statistical homogeneity that use redundant distance and spatial curvature measurements have been proposed, for example [53,54,55,56].…”
Section: Observing Dark Energy In the Era Of Large Surveys Plenary Spmentioning
confidence: 99%
“…Another advantage of the PCA is that there is no need to specify the cosmology; i.e. it is a model-independent approach, as the PCA will give us a set of functions that better describes the data [8], [9], [10], [11], [12], [13]. More details on the procedure of the PCA and the relevant sets of equations for each approach are also presented in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…What is particularly interesting for the coming decade are predictions for redshift evolution of Ω k , the average curvature parameter, from telescopes such as Euclid. Majerotto showed that statistically homogeneous and isotropic general-relativistic cosmological models in which the expansion rate history is observationally realistic, including the Timescape [40,99,100] and Tardis [45] models, have Ω k (z) relations that should be observationally distinguishable from ΛCDM to high significance by Euclid [95]. Both the models, as in the case of template metrics that match the supernovae type Ia distance-modulus-redshift relation, i.e., that of Ref.…”
Section: Recent Observational Resultsmentioning
confidence: 99%
“…Majerotto presented work together with Sapone and Nesseris [95] who applied the Clarkson, Bassett and Lu test [38,96] using eight H(z) cosmic chronometer estimates [97] (age of oldest passively evolving red galaxies at any given redshift z [98]) and a recent compilation of supernovae type Ia redshift-magnitude estimates. This test should distinguish some classes of relativistic or other non-FLRW models from the FLRW model.…”
Section: Recent Observational Resultsmentioning
confidence: 99%